MODERN IMPERATIVES OF SYSTEM-INNOVATIVE APPROACH TO THE SOLUTION OF ORGANIZATIONAL AND MANAGEMENT TASKS OF DIGITALIZATION OF BUSINESS PROCESSES - Anatolievich Doroshenko, Yuri; Somina, Irina; Nikulina, Olga (Journal of Applied Engineering Science, 2020)
This article substantiates the feasibility of applying systematic, integrated, factorial and process approaches to solving relevant organizational and managerial tasks of digitalization aimed at improving the efficiency of innovation and the competitiveness of economic systems. Substantial foundations of the implementation of a systems approach in the field of digital transformation of business processes were revealed. The advantages of digitalization were presented, possible basic problems associated with its implementation were systematized, and factors that have a significant impact on their solutions were analyzed. It is obvious that the exciting new possibilities of digital technologies are open to the world community and the urgent need for their large-scale implementation manifested itself, but taking into account the optimal combination of various factors that have a significant impact on the development of socio-economic systems.